2013
DOI: 10.1039/c3ob27238a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological studies of neopetrosiamides as inhibitors of cancer cell invasion

Abstract: The tricyclic peptides neopetrosiamides A and B, isolated from the marine sponge Neopetrosia sp., are potential antimetastatic agents that inhibit tumour cell invasion by both amoeboid and mesenchymal migration pathways. They differ in the stereochemistry of the methionine sulfoxide at position 24. Our previously reported syntheses using an orthogonal sulfur protection strategy established the critical connectivity of the three disulfide bonds. In this report, fifteen analogues of neopetrosiamide A and B, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…16 Being able to produce neopetrosiamide A synthetically has also facilitated structure/activity studies, which revealed the key role that the disulfide bonds play in defining the bioactive conformation of neopetrosamide A, as alternate disulfide isomers of this peptide were biologically inactive. 19 The marine sponge Geodia barretti Bowerbank (family Geodiidae, order Tetractinellida, class Demospongiae), a cold-water marine sponge found on the north Atlantic continental shelf, has been found to produce a wide range of secondary metabolites including several cyclic dipeptides derived from tryptophan and arginine, known as the barettins. 20−22 The barettins have recently been shown to act in synergy to deter larvae of surface settlers, 23 and field trials using barettins incorporated into paint were shown to prevent surface fouling by barnacles (Balanus improvisus) and blue mussels (Mytilis edulis).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Being able to produce neopetrosiamide A synthetically has also facilitated structure/activity studies, which revealed the key role that the disulfide bonds play in defining the bioactive conformation of neopetrosamide A, as alternate disulfide isomers of this peptide were biologically inactive. 19 The marine sponge Geodia barretti Bowerbank (family Geodiidae, order Tetractinellida, class Demospongiae), a cold-water marine sponge found on the north Atlantic continental shelf, has been found to produce a wide range of secondary metabolites including several cyclic dipeptides derived from tryptophan and arginine, known as the barettins. 20−22 The barettins have recently been shown to act in synergy to deter larvae of surface settlers, 23 and field trials using barettins incorporated into paint were shown to prevent surface fouling by barnacles (Balanus improvisus) and blue mussels (Mytilis edulis).…”
mentioning
confidence: 99%
“…Chemical synthesis of neopetrosiamide A using solid-phase peptide synthesis (SPPS) methods and an orthogonal cysteine protection strategy was subsequently used to determine the disulfide connectivity of the peptide . Being able to produce neopetrosiamide A synthetically has also facilitated structure/activity studies, which revealed the key role that the disulfide bonds play in defining the bioactive conformation of neopetrosamide A, as alternate disulfide isomers of this peptide were biologically inactive …”
mentioning
confidence: 99%
“…The sulfoxide group proved to be unnecessary for such activity, while disulde bond replacement led to complete activity loss. 235 Callipeltins B (114) and M (115), previously isolated from the marine sponge Callipelta sp., have been synthesized using solid-phase peptide synthesis of FMOC-protected amino acids, followed by lactonization with N,N 0 -diisopropylcarbodiimide and DMAP. 236 Polydiscamides B (116), C (117) and D (118) have also been synthesized, using solid-phase/Fmocprotected amino acids to generate the linear peptide 119 and the cyclodepsipeptide 120 moieties.…”
Section: Marine Spongesmentioning
confidence: 99%
“…They are potential antimetastatic agents that prevent tumour cell invasion by inhibition of both amoeboid and mesenchymal migration pathways [120]. …”
Section: Other Low Molecular Weight Marine Natural Compoundsmentioning
confidence: 99%